Enforceability of the legal provisions relating to special and diferential treatment under the WTO agreements - Kessie, Edwini (2000)
Examines the concept of special and differential treatment and how it has evolved in the multilateral trading system. Identifies five classes of special and differntial treatment provisions and discusses whether they are legally enforceable.